Reversing the stereoselectivity of a palladium-catalyzed O-glycosylation through an inner-sphere or outer-sphere pathway - Xiang, Shaohua (2015)
An efficient and concise method for the construction of various O-glycosidic bonds by a palladium-catalyzed reaction with a 3-O-picoloyl glucal has been developed. The stereochemistry of the anomeric center derives from either an inner-sphere or outer-sphere pathway. Harder nucleophiles, such as aliphatic alcohols and sodium phenoxides give β-products, and α products result from using softer nucleophiles, such as phenol.